Adipokinetic hormone enhances CarE‐mediated chlorpyrifos resistance in the brown planthopper, Nilaparvata lugens. Issue 6 (8th August 2020) - Tang, B.; Cheng, Y.; Li, Y.; Li, W.; Ma, Y.; Zhou, Q.; Lu, K.
Abstract: Adipokinetic hormone (AKH), the principal stress‐responsive neurohormone in insects, has been implicated in insect responses to insecticides. However, the functionality of AKH and its mode of signalling in insecticide resistance are unknown. Herein, we demonstrated that the enhanced activity of carboxylesterases (CarEs) is involved in the chlorpyrifos resistance in Nilaparvata lugens [brown planthopper (BPH)]. Chlorpyrifos exposure significantly induced the expression of AKH and its receptor AKHR in the susceptible BPH (Sus), and these two AKH signalling genes were over‐expressed in the chlorpyrifos‐resistant strain (Res) compared to Sus. RNA interference (RNAi) against AKH or AKHR decreased the CarE activity and suppressed the BPH's resistance to chlorpyrifos in Res. Conversely, AKH peptide injection elevated the CarE activity and enhanced the BPH's survival against chlorpyrifos in Sus. Furthermore, five CarE genes were identified to be positively affected by the AKH pathway using RNAi and AKH injection. Among these CarE genes, CarE and Esterase E4‐1 were found to be over‐expressed in Res compared to Sus, and knockdown of either gene decreased the BPH's resistance to chlorpyrifos. In conclusion, AKH plays a role in enhancing chlorpyrifos resistance in the BPH through positive influence on the expression of CarE genes and CarE enzyme activity. Abstract : Chlorpyrifos exposure induced the expression of AKH and AKHR in the susceptible brown planthopper (BPH), and these two genes were over‐expressed in the chlorpyrifos‐resistant BPH compared to the susceptible strain. CarE and Esterase E4‐1 were over‐expressed in the resistant BPH, and knockdown of either gene decreased the BPH's resistance to chlorpyrifos. Adipokinetic hormone plays a role in enhancing chlorpyrifos resistance in the BPH through positive influence on the expression of CarE genes and CarE enzyme activity.